Evaluación de impactos ambientales en el sistema de riego Vilcabamba - Castillo Vásquez, Víctor Emilio (2014)
The water universally is one of the most important and primordial resources to the human beings survival. This resource has an extensive use like in agriculture by guaranteeing the production of feeding to man and all animals. However, there are areas in our land that do not have access to enough quantity to this vital liquid. Nowadays the Ecuadorian State worried about to improve the conditions of life of the population, it is by fostering Irrigation system and albarradas, they are the options to supply of water to the dry zones of the country, an specific case is Vilcambamba irrigation system which it is operating in the parish, where the most of the year it is a dry area, benefiting immensely the agricultural and animal production. Moreover it has been generated environmental problems that they could not anticipate before this construction (1980), so it was not taken the methodology of evaluation of environmental impacts in our country. The irrigation system is located in the province of Loja, canton Loja, parish of Vilcabamba; on the left side of the Capamaco river, the study area are San Jose and Cucanama communities, covering an extension of 201,00 has, with a continuous flow of 165,60 l/s benefiting to 300 families. The evaluation of environmental impacts (Ex – Post), allows to determine the importance and magnitude of the negative impacts, generated by the implementation of the irrigation system and were not stabilised prior the construction. It was collected information of field and lab, which was analysed and interpreted with methodologies as it is the assessment matrix of environmental impacts, getting a broad and detailed vision of the different problems that face the sector, in the biotic, abiotic and socioeconomic aspect. With the matrix of the environment diagnostic, formed by dimensions, components elements and actions will be determined the interactions in which will be generated actions by the operation of the irrigation system and human activities. The social dimension has interactions, while the physical and the biotic in the same way will find out respectively The problematic about the environmental impact of the development on irrigation district continues being a prior theme of the development plans. The complexity of the interactions of the environmental process and the performance of the irrigation and drainage systems, it is such that is not always easy to predict which one will be the type and nature of the changes that may occur. The general objective of the work is to contribute to the improvement of the environmental quality through the evaluation of environment impacts resulting of the Vilcabamba irrigation system with an irrigate area of 201,00 ha, which it does the most important of the parish. The diagnostic executes on the analysis of secondary information, observations in field and interviews to qualified informers. The results of the studio inform that the effects of the environmental impact it is due to alterations on the hydrologic cycle or micro-watershed by human actions, due to changes on the hydric resource and for that similar to the management of the same system. With the gotten results with the convergence matrix, of importance and with the matrix of impact assessment that help to the positive and negative impacts and at the same time allow identify the corrective measures, the corrected measures that must be applied whether to minimize the negative impacts or maximize the positive ones; it is proposed later an environment management plan , that take advantage of all resources with the purpose of keeping and administrate them in the future, in such a way it establishes a balance in the ecosystem, assuring the preservation of the environment and improving the quality of the population